Strategies for Optimizing Teacher Service Quality through Strengthening Knowledge Management, Interpersonal Communication, Organizational Support, and Job Satisfaction - Andi Hermawan; Andri Kusuma Wardani; Endang Susilowati; Ulfiah Hanum (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study investigates strategies to improve the quality of teacher services in vocational high schools by examining the roles of knowledge management, interpersonal communication, organizational support, and job satisfaction. As vocational education serves as a cornerstone for human resource development, teacher performance plays a critical role in achieving its objectives. However, initial findings indicate that teacher service quality at PGRI Vocational High Schools in Bogor Regency remains below expectations, particularly in dimensions such as reliability, responsiveness, assurance, empathy, and tangibles. This research aims to propose actionable strategies to address these shortcomings by exploring the interrelationships among key variables. Adopting a mixed-method approach, the study utilized path analysis to test hypotheses regarding the relationships among variables and employed the SITOREM method to prioritize indicators for improvement. From a population of 289 teachers, a sample of 168 was selected using the Slovin formula. Data collection was conducted through validated and reliable questionnaires, followed by statistical analyses, including normality tests, regression analysis, and multicollinearity assessments, ensuring the reliability and robustness of the findings. The results demonstrated significant direct and indirect effects of knowledge management, interpersonal communication, and organizational support on job satisfaction and teacher service quality. Critical areas identified for improvement included knowledge acquisition, openness, fairness, and job satisfaction, while strengths such as knowledge utilization and group equity were highlighted for maintenance. The SITOREM analysis provided a structured approach to prioritize interventions, identifying fairness, supervisor support, and empathy as key areas for actionable improvement. This study emphasizes the interconnected role of leadership, effective communication, and supportive organizational structures in creating an environment conducive to high-quality teaching. Its findings contribute to the broader dialogue on enhancing teacher service quality in vocational education. Practical recommendations include implementing targeted training initiatives, revising institutional policies, and fostering supportive organizational cultures. While the study offers valuable insights, it acknowledges limitations such as its reliance on self-reported data and the contextual focus on vocational high schools. Future research is encouraged to include additional variables and expand the findings to different educational contexts. Keywords: teacher service quality, knowledge management, interpersonal communication, organizational support, job satisfaction, SITOREM analysis.